Strong Immunostaining for Myogenin in Rhabdomyosarcoma Is Significantly Associated with Tumors of the Alveolar Subclass - Dias, Peter (American Society for Investigative Pathology, 2000)
Rhabdomyosarcomas are a heterogeneous group of tumors with respect to their molecular basis, degree of differentiation, histology, and clinical behavior. Because of the wide variation of tumor morphology, it is often difficult to distinguish between the distinct subtypes of rhabdomyosarcomas. By using cryosections of tumor specimens and immunohistochemistry, in the present study we show that strong expression of myogenin in rhabdomyosarcoma is associated with alveolar histology (P = <0.0001, Fisher’s exact test). Although staining for myogenin was observed in 22 of 26 rhabdomyosarcomas, all alveolar rhabdomyosarcomas (nine of nine) showed high levels of staining for myogenin, as defined by the frequency and intensity of staining of the tumor cells. The staining pattern suggests that the tumor cells are clonally derived from myogenin-positive progenitor cells. In contrast, most embryonal rhabdomyosarcomas (13 of 15) were either negative or showed a low level of staining for myogenin. In these tumors a larger proportion of tumor cells were distinctly negative for myogenin. Six of seven alveolar rhabdomyosarcomas that strongly stained for myogenin were also positive for Pax3–7/Forkhead (FKHR) by polymerase chain reaction/reverse transcriptase-polymerase chain reaction. One of two embryonal rhabdomyosarcomas that strongly stained for myogenin was retrospectively found to be positive for Pax3/FKHR transcripts. Quantitative analysis for myogenin by Western blotting using a smaller subset of rhabdomyosarcomas revealed that in general there was a good correlation between immunohistochemical staining and Western blotting (P = 0.01, Pearson Correlation), although the former technique was more sensitive for detecting tumors with low levels of the protein. On average, alveolar rhabdomyosarcomas expressed at least threefold more myogenin than embryonal rhabdomyosarcomas. Our data show that staining for myogenin will be a simple, rapid, and accurate adjunct for distinguishing between alveolar and embryonal rhabdomyosarcomas. We propose that embryonal rhabdomyosarcomas result from an early block in myogenesis, before the expression of myogenin. In contrast, we propose that alveolar rhabdomyosarcomas either originate from a late block in myogenesis (after expression of myogenin) or that the pathological mechanisms involved in these neoplasms also induce strong expression of this protein.